The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1093/europace/eux376
|View full text |Cite
|
Sign up to set email alerts
|

Improving procedural and one-year outcome after contact force-guided pulmonary vein isolation: the role of interlesion distance, ablation index, and contact force variability in the ‘CLOSE’-protocol

Abstract: 'CLOSE'-guided PVI improves procedural and 1 year outcome in CF-guided PVI while shortening procedure time. Improvement cannot be explained by differences in CF variability and is most likely due to the strict application of criteria for contiguity and ablation index. A randomized controlled trial is needed to exclude the possible contribution of a learning curve.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

18
257
8
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 270 publications
(288 citation statements)
references
References 17 publications
18
257
8
5
Order By: Relevance
“…It can be assumed that extensive epicardial ablation reduced the extent and duration of endocardial ablation. Procedural times for RF CA of paroxysmal AF in recent studies were relatively short (as low as 120 minutes) and even shorter with cryoballoon procedure (as low as 110 minutes) compared to our study . However, published procedural duration times for PVI are not uniformly low.…”
Section: Discussioncontrasting
confidence: 63%
“…It can be assumed that extensive epicardial ablation reduced the extent and duration of endocardial ablation. Procedural times for RF CA of paroxysmal AF in recent studies were relatively short (as low as 120 minutes) and even shorter with cryoballoon procedure (as low as 110 minutes) compared to our study . However, published procedural duration times for PVI are not uniformly low.…”
Section: Discussioncontrasting
confidence: 63%
“…Compared to CF and FTI, AI which combines the latter three factors in a weighted equation has been shown to better correlate with lesion depth in an animal model . Recent studies have shown that AI‐guided ablation of atrial fibrillation is superior to CF‐guided ablation. A prospective study by Hussein et al showed that AI‐guided ablation of atrial fibrillation was associated with higher first‐pass pulmonary vein isolation, lower acute pulmonary vein reconnection and lower atrial tachyarrhythmia recurrence rate compared to CF‐guided ablation.…”
Section: Discussionmentioning
confidence: 99%
“…Ablation index (AI; CARTO 3 V4, Biosense Webster, Inc, Diamond Bar, CA), a novel marker of RF application quality that is calculated using a complex weighted exponential formula assigning different weights to power, CF and time, has been shown to accurately estimate lesion depth . AI‐guided ablation is associated with significant improvements in the incidence of acute pulmonary veins reconnection and atrial tachyarrhythmia recurrence rate compared to CF‐guided ablation . However, there is no systematic study on the efficacy of AI‐guided ablation of CTI which is the aim of this study.…”
Section: Introductionmentioning
confidence: 99%
“…Our data indicate that AI‐guided ablation may also be safe in regard to creating low incidences of EDELs by potentially reducing local energy and ablation time to a minimum needed for adequate lesion formation but not more. AI‐guided ablation has been documented to improve the procedural and long‐term outcome of AF ablation but randomized trials documenting efficacy on the one hand and safety on the other hand are lacking …”
Section: Discussionmentioning
confidence: 99%
“…These parameters might also predict the risk of postprocedural esophageal thermal lesions (EDELs) induced by RF ablation at posterior left atrial (LA) wall. In a recent study, improved acute and 12‐month efficacy were documented using ablation index (AI)—a novel parameter defining energy application at single ablation sites, calculated by integration of catheter stability, ablation time, ablation energy, and contact force—to guide local RF applications …”
Section: Introductionmentioning
confidence: 99%